High-Field (13)C DNP with a Radical Mixture - Michaelis, Vladimir K. (2013)
We report direct (13)C dynamic nuclear polarization at 5 T under magic angle spinning (MAS) at 82 K using a mixture of monoradicals with narrow EPR linewidths. We show the importance of optimizing both EPR linewidth and electron relaxation times by studying direct DNP of (13)C using SA-BDPA and trityl radical, and achieve (13)C enhancements above 600. This new approach may be better suited for dissolution DNP and for studies of (1)H depleted biological and other non-protonated solids.